Structural, optimization of and mechanistic insights into a new thiosemicarbazone derivative as a highly sensitive and selective chemosensor for Hg2+ recognition using DFT, COSMO-RS, RSM, and molecular dynamics simulation approaches - Ismail, Hakimah; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya (Elsevier, 2023)
A new thiosemicarbazone derivative, N-(2-hydroxyphenyl)-2-[1-(pyridin-4-yl)ethylidene]hydrazinecarbothioamide (HPEH), has been synthesized, characterized, and further developed as a highly selective and sensitive colorimetric chemosensor for Hg2+ recognition in environmental water samples. Structural conformers of HPEH were successfully identified using a combination of the potential energy surface (PES) and time-dependent density functional theory (TD-DFT) methods. The synthesized HPEH was successfully characterized further and analyzed based on its harmonic vibrational frequencies, NMR spectra, and electronic transitions using the DFT approach. Sigma profiles were generated using the COSMO-RS approach to identify a compatible medium for HPEH to act as a chemosensor. The conditions for the highly sensitive and selective detection of Hg2+ by HPEH were successfully optimized using the statistical response surface methodology approach. The optimum sensing of HPEH occurred in an 8:2 v/v DMSO/pH 7.8 solution at a 20:60 μM HPEH/Hg2+ concentration and after a reaction time of 18 minutes, with statistically significant independent variables (p < 0.05) for all parameters. The lowest Hg2+ concentration detected by HPEH under the optimum conditions was 3.56 µM, which is lower than that for other previously reported Hg2+ chemosensors. Using the optimized results, the interaction between HPEH and Hg2+ in the chemosensor system was successfully modeled, and the model was subsequently used with the TD-DFT, non-covalent interaction-reduced density gradient (NCI-RDG), and molecular dynamics approaches to gain mechanistic insights into the interaction. The results showed that the newly synthesized HPEH, in addition to being cost-effective, could serve as a suitable alternative and comparable chemosensor for Hg2+ recognition in water samples, with the advantages of being efficient, portable, and eco-friendly, and offering rapid analysis without the need of specialized training.